Prevalence and predictors of iron deficiency anaemia in adolescent girls in India - Baruah, Akanksha; Gautam, Sarita (International Journal Of Community Medicine And Public Health, 2023)
Background: In India, iron deficiency anaemia is highly prevalent, particularly among women of reproductive age group. Following early childhood, during adolescence, the risk of iron deficiency and anaemia reappears for both boys and girls, but remains more susceptible to girls because of menstrual loss. The aim of this study was to find the prevalence and predictors of iron deficiency anaemia in adolescent girls in India. Methods: This study was a descriptive form of review of literature on data from comprehensive national nutrition survey (CNNS 2016-2018). CNNS was conducted to collect data on the nutritional status of Indian children from 0-19 years of age. The data collection period was from 26 February 2016 to 24 October 2018 and data was collected using individual and household questionnaires. Results: In the study, prevalence of various levels of anaemia (mild, moderate and severe) was higher in adolescent girls as compared to adolescent boys. Adolescent girls had 31.3% iron deficiency whereas adolescent boys had 11.5% iron deficiency. Anaemia prevalence was also higher in the age group 15-19 years as compared to 10-14 years. Conclusions: It was concluded that iron deficiency anaemia was more prevalent in adolescent girls than boys. Inadequate intake of iron rich foods and vitamin C, less knowledge about anaemia, low socio economic conditions along with poor hygiene and sanitation practices are the major factors that contribute to iron deficiency anaemia.